2019
DOI: 10.17628/ecb.2019.8.7-14
|View full text |Cite
|
Sign up to set email alerts
|

New Thiazolone Derivatives: Design, Synthesis, Anticancer and Antimicrobial Activity

Abstract: In order to explore the anticancer and antimicrobial activity associated with the thiazolone framework, several new (Z)-2-((5-(3fluorobenzylidene)-4-oxo-4,5-dihydrothiazol-2-yl)amino)carboxylic acid derivatives have been synthesized in water as a solvent. All synthesized compounds were evaluated for anticancer and antimicrobial activity in vitro. Amongst these, the 3-methylbutanoic and the 3-or 4-methylpentanoic acid derivatives, the 3-hydroxy-, the 3-(1H-imidazol-4-yl) and the 3-(4-hydroxyphenyl)propanoic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…In this work, two derivatives of 2-thiohydantoin, compound A (5-benzylidene-2-thiohydantoin-3-acetic acid) and compound B (5-cinnamylidene-2-thiohydantoin-3-acetic acid), have been synthesised. The antifungal activity of similar compounds was detected [13,32,33], so we expect that compounds synthesised here also can have this property. Studies on their antifungal properties are currently being conducted.…”
Section: Resultssupporting
confidence: 54%
“…In this work, two derivatives of 2-thiohydantoin, compound A (5-benzylidene-2-thiohydantoin-3-acetic acid) and compound B (5-cinnamylidene-2-thiohydantoin-3-acetic acid), have been synthesised. The antifungal activity of similar compounds was detected [13,32,33], so we expect that compounds synthesised here also can have this property. Studies on their antifungal properties are currently being conducted.…”
Section: Resultssupporting
confidence: 54%
“…With reference to above literature survey, in continuation to our previous research work of pharmaceutical moieties, 30–36 we have focused on synthesis of imidazo[1,2‐ a ]pyrimidine‐3‐carbonitrile derivatives (4a‐j ) using efficient and heterogeneous Zinc Ferrite (ZnFe 2 O 4 ) as nanocatalyzed one‐pot three‐component condensation reaction of benzimidazole ( 1 ) and malononitrile (3) with substituted aromatic aldehyde (2a‐j ) in methanol under ultrasonic irradiations. Author has selected normal spinel catalyst ZnFe 2 O 4 for present synthesis because ammonia molecule preferred to adsorbed on the surface of Zn atom of spinal zinc ferrite and it is used to removal of ammonia 37 .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] These reports suggested that Rhodanine nuclei were essential to the observed levels of antimicrobial activity. [25][26][27][28] We make a plan to synthesized Rhodanine derivatives as an antimicrobial agent by preparing hybrid molecules having similar features of reported potent antimicrobial agents (Figure 1). Because of the facts mentioned above, Rhodanine derivatives were synthesized, characterized by different spectral analysis techniques and screened for their antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%